Antioxidant, Anti-Inflammatory and Anti-diabetic Efficiency of Indian Medicinal Plants against Streptozotocin Induced Diabetes in Male Wistar Rats - Vemuri, Satish Kumar; Banala, Rajkiran Reddy; Katragunta, Kumar; Madhuri, Vijaya; Raju, Kiruthika; Annapareddy, Venkata Gurava Reddy; Goli, Pedda Venkata Subbaiah (Free Radicals and Antioxidants)
Objective: The study was aimed to assess the anti-oxidative and anti-diabetic efficacy of few dietary supplements such as Artocarpus heterophyllus (Raw Jackfruit), Zea mays (Corn Silk), Syzygium cumini (Black plum), and Shilajit (Black asphaltum) in in vitro and in vivo models. The phytoextracts were compared with the known commercial diabetic drugs (Aminoguanidine, Glibenclamide and Insulin) in controlling Streptozotocin induced hyperglycemia, advanced glycation end-products (AGEs), hyperlipidemia and activation of inflammatory mediators (iNOS) in in vivo. Methods: Collection and preparation of phytoextracts, superoxide anion scavenging assay, phosphomolybdate assay (total anti-oxidant capacity), Hydroxyl radical scavenging assay, quantification of hemoglobin glycation, body weights, lipid profile, Pro-inflammatory gene expression, agarose gel electrophoresis and histopathology. Results: We found that natural extracts of A. heterophyllus, S. cumini, Z. mays, and Shilajit exhibited considerable antioxidant capacity and inhibited hemoglobin glycosylation in a dose-dependent manner in in vitro. In STZtreated diabetic rats, the extracts showed clear effects on blood glucose and lipid levels, body weight and pro-inflammatory gene expression (iNOS). Histopathology of treated rat pancreas further supported our in vivo findings. Overall, our study indicates that the natural extracts we tested could be a useful source of antioxidant agents, functional foods and nutraceuticals, particularly in diabetes and related complications. Conclusion: The findings from our study showed reversal of the effects induced by Streptozotocin administration on phytoextracts supplementation in experimental diabetic rats and the therapeutic capacity was similar to that of commercial diabetic drugs, hence these extracts could serve as an alternate in management of diabetes and allied complications.
Keywords: Medicinal plants; Streptozotocin (STZ); Glycation; Glycosylated hemoglobin; iNOS